The moving gardens: Reef fishes grazing, cleaning, and following green turtles in SW Atlantic - Sazima, C.; Grossman, A.; Bellini, C.; Sazima, I (Soc Francaise D Ichtyologie, 2004)
Reef fishes may associate with marine turtles and graze on their shells, or clean their head, neck and flippers. on a reef flat at Fernando de Noronha Archipelago, SW Atlantic, we recorded green turtles (Chelonia mydas) grazed, cleaned and followed by reef fishes. The green turtle seeks specific sites on the reef and pose there for the grazers and/or cleaners. Fishes recorded associated to green turtles included omnivorous and herbivorous reef species such as the dam-selfish Abudefduf saxatilis and the surgeonfishes Acanthurus chirurgus and A. coeruleus. The turtle is followed by the wrasse Thalassoma noronhanum only while engaged in foraging bouts on benthic algae. Following behaviour is a previously unrecorded feeding association between turtles and fishes.
Keywords: Acanthuridae; Pomacentridae; Labridae; Chelonia mydas; ASW; fish foraging; symbiosis